Business terms enrichment by using own flash card - Irmawati; Andy Cubalit (International Journal of Humanities and Innovation (IJHI), 2018)
Vocabulary is the foundation of the language. It is used to communicate for both oral and written communication. Business terms are used to communicate in the business world activities. It may relate to economics, accounting, banking, tourism, hotel, and others business field. This paper focused on the use of flash cards in enriching the students’ business terms mastery based on the writers’ experience. There are some activities may occur in the classroom by using flashcards. It is classified as memory activity, drilling activity, identification, and Total Physical Response (TPR) activity. They are an abundant approach to present, practice, and recycle vocabulary.